Archaeology and bioarchaeology of anatomical dissection at a nineteenth-century army hospital in San Francisco - Willey, Patrick S.; Gavette, Peter; Bartelink, Eric J.; Milligan, Colleen F. (Bioarchaeological interpretations of the human past., 2023)
"This volume uses historical, archaeological, and bioarchaeological analysis to study and understand a nineteenth-century medical waste pit discovered at the former Army hospital at Point San Jose in San Francisco"--